Ontogenetic variation in skull shape of Thrichomys apereoides (Rodentia : Echimyidae) - Monteiro, L. R.; Lessa, L. G.; Abe, Augusto Shinya [UNESP] (Amer Soc Mammalogists, 1999)
The pattern of change in shape during postnatal development in skulls of punare (Thrichomys apereoides) skulls, was studied by geometric morphometric techniques. Skull shape observed in T. apereoides varied both with size and age, but variation in size explains most of the overall change in shape. Differences in shape observed among the eight age categories showed that main changes in shape occurred principally between the first and second age categories. Among the other age classes, changes became less pronounced leading to elongation of the snout and the mid-face and narrowing of the basicranium. The change in global shape resulted in lateral compression of the skull. Despite the high level of integration observed, localized transformations dominated the ontogenetic changes in shape indicating the presence of two large scale cranium components-the orofacial and the basicranial region. The ontogenetic pattern in this species seems to follow the same trends observed in the initial phases of development.
Keywords: Thrichomys; morphological integration; geometric morphometrics; multivariate regression; skull; ontogeny